2017
DOI: 10.1002/nbm.3801
|View full text |Cite
|
Sign up to set email alerts
|

Region‐specific impairment of the cervical spinal cord (SC) in amyotrophic lateral sclerosis: A preliminary study using SC templates and quantitative MRI (diffusion tensor imaging/inhomogeneous magnetization transfer)

Abstract: In this preliminary study, our objective was to investigate the potential of high-resolution anatomical imaging, diffusion tensor imaging (DTI) and conventional/inhomogeneous magnetization transfer imaging [magnetization transfer (MT)/inhomogeneous magnetization transfer (ihMT)] at 3 T, analyzed with template-extracted regions of interest, to measure the atrophy and structural changes of white (WM) and gray (GM) matter spinal cord (SC) occurring in patients with amyotrophic lateral sclerosis (ALS). Ten patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 59 publications
4
48
2
Order By: Relevance
“…Conditioned medium from glial cells exposed to ALS-CSF also resulted in reduced viability of NSC-34 cells [31,41]. The reduction in the white matter area observed with staining by phospohorylated neurofilaments can be correlated to white matter atrophy observed in ALS patient spinal cord [49]. Based on these data, it could be assumed that CHIT-1 primarily activates microglia while astrocytes respond to activated microglia and join to evoke a sustained toxicity resulting in the release of proinflammatory molecules, which can further lead to neuronal death (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Conditioned medium from glial cells exposed to ALS-CSF also resulted in reduced viability of NSC-34 cells [31,41]. The reduction in the white matter area observed with staining by phospohorylated neurofilaments can be correlated to white matter atrophy observed in ALS patient spinal cord [49]. Based on these data, it could be assumed that CHIT-1 primarily activates microglia while astrocytes respond to activated microglia and join to evoke a sustained toxicity resulting in the release of proinflammatory molecules, which can further lead to neuronal death (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The first approach is JIM v6 (Xinapse Systems, http://www.xinapse.com) that was previously used in different studies . The second approach is the open source Spinal Cord Toolbox (SCT) (https://sourceforge.net/p/spinalcordtoolbox/wiki/Home/) that has seen recent utilization …”
Section: Methodsmentioning
confidence: 99%
“…In addition to this strong contrast for myelinated tissues, the ihMT technique also benefits from trivial processing, simply based on the subtraction of a minimum of 2 MT images obtained with different radiofrequency (RF) irradiation parameters. Overall, these properties have made ihMT an attractive method to assess myelin-related information in vivo, in the clinical context of demyelinating diseases (Rasoanandrianina et al, 2017;Van Obberghen et al, 2018) or in the context of aging studies (Geeraert et al, 2017;Taso et al, 2016). In addition, other studies have shown that the ihMT signal correlates with established myelin-sensitive MR imaging techniques such as myelin water fraction (MWF) (Ercan et al, 2018;Geeraert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%